Analisa Kuat Arus Listrik dan Waktu Electroplating Nickel-Chrome terhadap Kekerasan dan Ketebalan Lapisan Permukaan Baja Karbon Rendah - Sumpena Sumpena; Wardoyo Wardoyo (Jurnal Engine: Energi, Manufaktur, dan Material, 2021)
The metal plating industry needs not only for corrosion resistance, but also for the strength of the material, having a decorative appearance, and having high economic value. Several types of coatings can be used to prevent or slow down the level of damage and increase the mechanical strength of the metal, one of which is  electroplating. The purpose of this study was to determine the effect of variations in electric current strength and time of electroplating nickel-chrome on the hardness and thickness of the surface layer of low carbon steel. Experiments were carried out by observing changes in the independent variables, namely the electroplating process time of 10 minutes, 15 minutes, and 20 minutes. The controlled variable in this study is the 5 Ampere power supply current. While the current strength used in this study is 0.5 A, 1 A and 1.5 A. The test results show the electroplating process with a strong current of 0.5A in 10, 15 and 20 minutes, namely 132.63 VHN, 189.03 VHN, and 172.36 VHN. The electroplating process with a current of 1A obtained hardness values of 201.66 VHN, 187.96VHN, and  187.53VHN. The electroplating process with a current of 1.5A obtained hardnessvalues of 191.13VHN, 195.1VHN, and 182.13VHN. The highest hardness was at 1A, the coating time was 10 minutes. While the lowest hardness was at 0.5A current,  the coating time was 10 minutes.